2021
DOI: 10.3390/molecules26061520
|View full text |Cite
|
Sign up to set email alerts
|

Direct Flavonoid-Focused Chemical Comparison among Three Epimedium Plants by Online Liquid Extraction–High Performance Liquid Chromatography–Tandem Mass Spectrometry

Abstract: It is usually a tedious task to profile the chemical composition of a given herbal medicine (HM) using high performance liquid chromatography–tandem mass spectrometry (LC–MS/MS) due to the time-consuming sample preparation and laborious post-acquisition data processing procedures. Even worse, some labile compounds may face degradation risks when exposed to organic solvents for a relatively long period. As one of the most popular HMs, the promising therapeutic benefits of Epimedii Herba (Chinese name: Yinyanghu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Taking peak 105 as an example, in the ESI + mode, the quasi‐molecular ion peak of m/z 839.2977 [M+H] + can be detected in the low collision energy mass spectrum with the retention time of 9.94 min. At the same time, high collision energy mass spectrometry showed that the main fragment ions were 677.2443 [M+H‐glc] + , 531.1879 [M+H‐glc‐rha] + , 369.1356 [M+H‐glc‐rha‐glc] + , it can be inferred that the compound may be Epimedin A1 [26–28]. This idea led to the characterization of 8 flavonoid glycosides, whose structures and the identification process, fragmentation pathway of Epimedin A1 based on QI are displayed in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…Taking peak 105 as an example, in the ESI + mode, the quasi‐molecular ion peak of m/z 839.2977 [M+H] + can be detected in the low collision energy mass spectrum with the retention time of 9.94 min. At the same time, high collision energy mass spectrometry showed that the main fragment ions were 677.2443 [M+H‐glc] + , 531.1879 [M+H‐glc‐rha] + , 369.1356 [M+H‐glc‐rha‐glc] + , it can be inferred that the compound may be Epimedin A1 [26–28]. This idea led to the characterization of 8 flavonoid glycosides, whose structures and the identification process, fragmentation pathway of Epimedin A1 based on QI are displayed in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, most of the detected compounds are not available for procurement and are present in minor amounts, which makes the isolation cost-inefficient. To overcome this, while still being able to use the data for relative comparisons between phytochemical profiles, one can use various approaches, such as fragmentation patterns [ 35 , 36 , 37 , 38 , 39 , 40 ], supported by a library search (used mainly in the present paper) or coupling (offline) to NMR spectroscopy [ 41 ]. The latter provides much more accurate structural information but is also less affordable and more laborious.…”
Section: Discussionmentioning
confidence: 99%
“…The LC–MS approach used in this study was based on the m / z -retention time pairs and normalized signals values to calculate the multivariate correlations and discrimination, an approach often used to compare plant samples within a taxon along with more advanced techniques [ 35 , 37 , 38 , 39 , 40 ], which allows compensating the lack of most phytochemical standards. Nonetheless, for absolute values, the standard-based quantification is advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…Epimedii Folium was rich in flavonoids featured with isopentenyl substitution. After applying the empirical rules and referring to the information archived in the literature [24], a total of 70 flavonoids (Table S1) were tentatively characterized. In particular, four identities were justified by matching chromatographic and spectrometric information with authentic compounds, such as epimedium A, epimedin B, epimedin C, and baohuoside I.…”
Section: Chemical Profile Characterization Of Single Medicinal Materi...mentioning
confidence: 99%
“…After the harvest of a massive MS/MS dataset, the heavy workload subsequently turns to extracting valid information at the meanwhile of omitting the redundant information. In the past years, some meaningful post‐acquisition data processing strategies [22] have been proposed, such as neutral loss filtering [23], mass defect filtering [24], diagnostic fragment ion filtering [25], molecular weight imprinting [20] and mass tree filtering [26]. However, these approaches are still time‐consuming.…”
Section: Introductionmentioning
confidence: 99%